State Institutional Capacities in a Comparative Perspective: An Experience of Bayesian Aggregation of State Capacity Index - I. Ye. Gorelskiy (Сравнительная политика, 2024)
This article endeavors to construct a composite indicator designed to facilitate the comparative assessment of institutional capacities across diverse political systems. The focal point of analysis resides within the domain of state capacity, a pivotal determinant for a myriad of inquiries that seek to evaluate the efficacy of public policy implementation across varying spheres. The attainment of the research objective materialized through the adoption of Bayesian methodologies tailored for the scrutiny of latent variables, a prevalent recourse within contemporary social sciences to address analogous empirical puzzles. Drawing upon antecedent advancements collaboratively undertaken with co-authors and a minimal selection of variables, ranging from the comprehensive gauge of control over violence to formal economic activity (reciprocally aligned with the gauge of informal economy), two distinct models were subjected to empirical examination: namely, the linear and hierarchical ones. The ensuing analysis of 150 countries across three temporal junctures (1996, 2005, and 2015) distinctly advocates for the adoption of the latter model after accommodating convergence testing. The hierarchical model, oriented towards encapsulating the tripartite dimensions of state capacity, namely administrative, coercive, and extractive facets, gains preference. This predilection aligns with the contribution of J. Hanson and R. Sigman, whose conceptual underpinnings are frequently espoused by scholars when delineating the contours of the observed construct. The hierarchical model affirms the efficacy and discriminatory acumen of the proposed approach in engendering pertinent state rankings. These empirical revelations, in turn, constitute an indispensable stride towards interrogating assorted hypotheses concerning trajectories of institutional development and the construction of classificatory frameworks delimiting state capacity. Moreover, they extend utility in the realm of comparative studies by furnishing an aggregated indicator conducive to cross-national analysis.